2005
DOI: 10.1021/ol051879w
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrogenation of Dihydropyrimidinones and Dihydropyrimidines

Abstract: [reaction: see text] A mild, practical procedure for oxidative dehydrogenation with catalytic amounts of a Cu salt, K2CO3, and tert-butylhydroperoxide (TBHP) as a terminal oxidant has been developed. This oxidation procedure is generally applicable to dihydropyrimidinones and most dihydropyrimidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 28 publications
0
57
0
1
Order By: Relevance
“…Besides, these results quite agree with the studies of the oxidation processes of related dihydro pyrimidine structures conducted earlier. 21,22 In crystal, the molecule of rac (7(7A)R*,9(9A)S*) isomer 11 (see Fig. 6) occupies a particular position on the second order axis passing through the center of the C(9)-C(9A) bond.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, these results quite agree with the studies of the oxidation processes of related dihydro pyrimidine structures conducted earlier. 21,22 In crystal, the molecule of rac (7(7A)R*,9(9A)S*) isomer 11 (see Fig. 6) occupies a particular position on the second order axis passing through the center of the C(9)-C(9A) bond.…”
Section: Resultsmentioning
confidence: 99%
“…Attachment of two electronwithdrawing groups, CF 3 /Cl and CF 3 /CN, also afforded 22 and 23, respectively, in good yields (entries 13 and 14). Bicyclic 1-iodonaphthalene producing 24 and heterocyclic iodopyridine and iodothiophene were also suitable reaction partners (entries [15][16][17][18][19]. Regarding the position of the heteroatom in these heterocyclic aryl iodides, 2-iodopyridine afforded the corresponding product in a higher yield (90%, 25) than 3-iodopyridine (76%, 26), while similar yields were observed for iodothiophene (86%, 27 vs. 89%, 28).…”
Section: Methodsmentioning
confidence: 99%
“…Higher temperature (90 °C) resulted in a two-fold increase in the reaction yield in DMF or NMP, while insignificant improvement was observed for toluene or dioxane, or a low yield at reflux in BuOAc, i-PrOH, or 2-MeTHF (entries [6][7][8][9][10][11][12]. Thus, we performed the reaction in DMF or NMP with a gradual increase in temperature and observed that the reaction yield increased up to 130 °C and that NMP was a superior solvent compared to DMF (entries [13][14][15][16][17][18]. The reaction under O 2 resulted in lower yield than that under air (entry 19).…”
Section: Methodsmentioning
confidence: 99%
“…For this, we used oxidative dehydrogenation conditions with catalytic amounts of CuCl 2 , potassium carbonate and tert-butylhydroperoxide (TBHP) as oxidant (Scheme 1). 9 Instead of nucleoside 4, the 5,5 0 -cyclonucleoside 6 was formed. The NMR data of this compound differ significantly from that of 3.…”
Section: Synthesis Of Nucleoside and Phosphoramiditementioning
confidence: 99%